Developing National Priorities for the Forest-Based Sector Technology Platform - Ville Brummer; Totti Konnola; Ahti Salo (Foresight and STI Governance)
Although foresight has become increasingly relevant at the international level, little methodological attention has been given to the challenges that arise from the geographical dispersion of participants or the consideration of their national and regional idiosyncrasies.This paper addresses these challenges in connection with coordination tools for the ‘Open Method of Coordination’ — most notably ERA-NETs and European Technology Platforms — which are facilitated by the European Commission with the aim of contributing to the establishment of the European Research Area (ERA). Specifically, it is argued that the successful management of these tools calls for multi-stakeholder processes which pose demands such as scalability, modularity and dependability on the design and deployment of foresight methodologies.The authors report experiences from a recent foresight process that was conducted in Finland to support the development of the Strategic Research Agenda (SRA) of the Forest-Based Sector Technology Platform. The encouraging results from this process and the broader potential of internet-based decision support systems are discussed in view of European coordination tools.